Potential of laponite incorporated oxidized alginate–gelatin (ADA-GEL) composite hydrogels for extrusion-based 3D printing - Cai, Fei Fan; Heid, Susanne; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2020)
The concept of adding inorganic fillers into hydrogels to form hydrogel nanocomposites often provides advantageous properties which can be exploited for successful 3D biofabrication. In this study, a new composite hydrogel combining oxidized alginate–gelatin (ADA-GEL) hydrogel and laponite nanoclay as inorganic nanofiller was successfully developed and characterized. The results showed that the addition of 0.5% (wt/vol) laponite nanoplatelets improved the printability of ADA-GEL hydrogels enabling the fabrication of detailed structures since a low effect of material spreading and reduced tendency to pore closure appeared. Furthermore, a comparison of different needle types (cylindrical and conical; same inner diameter of 250 μm) in filament fusion test showed that the pattern dispensed by cylindrical tip has enhanced printing accuracy and pattern fidelity when compared with the pattern from conical tip. A glass flip test determined a processing window of 1–2 h after composite ink preparation. Overall, laponite/ADA-GEL hydrogel composites are confirmed as promising inks for 3D bioprinting.
CRIS-Team Scopus Importer:2020-12-11
Keywords: ADA-GEL; biomaterial; bioprinting; composite; hydrogel; laponite; nanoclay; scaffold; tissue engineering